2015
DOI: 10.18632/oncotarget.3365
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression analysis of CD133 and CD44 identifies Proneural and Mesenchymal subtypes of glioblastoma multiforme

Abstract: Accumulating evidence suggests that the stem cell markers CD133 and CD44 indicate molecular subtype in Glioblastoma Multiforme (GBM). Gene coexpression analysis of The Cancer Genome Atlas GBM dataset was undertaken to compare markers of the Glioblastoma Stem-Progenitor Cell (GSPC) phenotype. Pearson correlation identified genes coexpressed with stem cell markers, which were then used to build a gene signature that classifies patients based on a CD133 coexpression module signature (CD133-M) or CD44-M subtype. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 61 publications
7
72
0
1
Order By: Relevance
“…It has been demonstrated previously that the invasive behavior exhibited by glioma cells hinges on the coordinated activation of multiple cell signaling pathways (3,5,50). For the most aggressive TPC cells, that is, those of the mesenchymal hGBM cluster, this translates into a specific signature in which cell motility, migration, and aggressiveness pathways are enriched (39,40,49). Our analysis identified this molecular module in highly invasive Wnt5a…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It has been demonstrated previously that the invasive behavior exhibited by glioma cells hinges on the coordinated activation of multiple cell signaling pathways (3,5,50). For the most aggressive TPC cells, that is, those of the mesenchymal hGBM cluster, this translates into a specific signature in which cell motility, migration, and aggressiveness pathways are enriched (39,40,49). Our analysis identified this molecular module in highly invasive Wnt5a…”
Section: Discussionmentioning
confidence: 58%
“…S1E). Strikingly, the expression levels of the genes associated with the Wnt-Ca 2þ signaling pathway were higher in tissues from mesenchymal hGBMs, which are endowed with higher aggressiveness and invasiveness (38)(39)(40) as compared with healthy brain tissues (Fig. 1C).…”
Section: Wnt5a Overexpression In the Most Infiltrative High-grade Glimentioning
confidence: 99%
“…This previously unidentified relationship between MDA-9 and CSCs, on multiple molecular levels, emphasizes the significance of this gene as a potential new exciting therapeutic target. CD133 a proneural GBM CSC and poor prognosis marker, as wells as CD44, a characteristic marker for mesenchymal GBM CSCs (Brown et al, 2015;Mao et al, 2013;Wang et al, 2009) were both significantly downregulated post mda-9 knock-down (unpublished observation). These results indicate the efficacy of MDA-9 in regulation of CSCs at multiple levels ( Fig.…”
Section: Mda-9/syntenin (Sdcbp)mentioning
confidence: 85%
“…19 CD44 belongs to glioblastoma cancer stem cell (CSC) markers and might promote cancer cell stemness by interacting with ECM components, growth factors and cytokines. 20,21 CD44 protein marker expression correlates with molecular subtype of GBM 22 and positively associated with radioresistance of glioblastoma. 23 Data on the prognostic significance of CD44 in glioblastoma are controversial -it was suggested that enhanced CD44 expression is associated with poor survival rates in glioblastoma although this finding was not statistically significant; 24 lower levels of CD44 expression surprisingly correlated with lower survival for GBM patients.…”
Section: Introductionmentioning
confidence: 99%